Effects of Moringa oleifera leaf extract combined with DFBBX on type-1 collagen expressed by osteoblasts in the tooth extraction sockets of Cavia cobaya - S. Soekobagiono; Sherman Salim; Hanoem Eka Hidayati; Karina Mundiratri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Tooth extraction is a common procedure in dentistry after which the residual ridge will no longer receive stimulus leading to volume, height and width loss. These anatomical changes can then result in difficulties with future denture fabrication and implant placement. Preservation of the alveolar ridge, therefore, assumes considerable importance after tooth extraction. Moringa oleifera, on the other hand, can enhance bone formation. Type-1 collagen is a marker of osteoblast formation. Purpose: This research aimed to analyze the effects of Moringa oleifera leaf extract combined with DFBBX on type-1 collagen expressions in tooth extraction sockets. Methods: 56 Cavia cobaya subjects were divided into eight groups. Their lower left incisors were then extracted prior to the sockets of the first and fifth groups being filled with PEG, those of the second and sixth groups with DFBBX, those of the third and seventh groups with Moringa oleifera leaf extract and a combination of DFBBX and Moringa oleifera leaf extract in those of the fourth and eighth groups. The sockets were then examined on days 7 and 30 by means of an immunohistochemical technique. The data collected was subsequently subjected to analysis by One Way Anova and Tukey HSD tests. Results: There were significant differences between the control group and the treatment group administrated with Moringa oleifera leaf extract combined with DFBBX. On days 7 and 30, the groups treated with the combination of DFBBX and Moringa oleifera leaf extract had the highest number of type-1 collagen expressions. Conclusion: A combination of DFBBX and Moringa oleifera leaf extract is effective in increasing type-1 collagen expressions in tooth extraction sockets.